PENGARUH SHUTTLE RUN INTERVAL TERHADAP VERTICAL JUMP PERFORMANCE PEMAIN BASKET DI BUDI DHARMA BASKETBALL CLUB - Ezra Widodo; Sartoyo Sartoyo; Nurul Halimah; Angria Pradita (Kieraha Medical Journal, 2026)
Basketball is a dynamic and high-intensity sport that requires explosive jumping capability. Vertical jump performance is a crucial physical attribute supporting actions such as shooting, rebounding, and blocking. The shuttle run interval training method is assumed to induce neuromuscular and anaerobic energy system adaptations directly correlated with increased lower extremity explosive power in players. This study aimed to analyze the effect of shuttle run interval training on enhancing vertical jump performance in basketball players at the Budi Dharma Basketball Club, Pasuruan City. This quantitative study employed a pre-experimental design (one-group pretest-posttest design) involving 17 male basketball players aged 16–19 years, selected via purposive sampling. The shuttle run interval training intervention was administered twice weekly over a four-week period. The measurement instrument used to assess vertical jump performance was the Sargent Jump Test. Data normality was assessed using the Shapiro-Wilk test, and analysis was conducted using the Paired Sample T-Test. The results demonstrated a significant improvement in vertical jump across all subjects. The mean vertical jump performance score was 43.47 cm prior to the intervention (pre-test) and significantly increased to 49.23 cm following the intervention (post-test), with a p-value of 0.000 ($p < 0.05$). The shuttle run interval training program proved to have a significant effect on enhancing the vertical jump performance of basketball players through the optimization of the functional explosive power of lower extremity muscles